Development of a Mobile Application for Robust Tuning of One- and Two-Degree-of-Freedom PI and PID Controllers - Arrieta Orozco, Orlando (2015)
This paper presents the development of a mobile application for Android systems devices, that helps in the control system design task. The application allows to compute the parameters of PID-type controllers. The controlled process can be represented by a first- or second-order plus dead-time model and from that, the application tunes 1DoF PI and PID controllers for servo and regulatory control operation, and 2DoF PI and PID controllers, using methods presented in Alfaro and Vilanova (2012a,b). It is shown the use of the application tool where it is possible to evaluate benefits for the control systems undergraduate students. This is one of the main contributions from the educational point of view.